Past and future of stem cells: from Prometheus to regenerative medicine - Faa, Gavino; Fanos, Vassilios; Giordano, Antonio (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2016)
The salamander limb regenerates completely after amputation and the heart of the zebrafish returns to normal even after an extensive injury. What is it that makes all this possible? The answer is the presence of stem cells, which in these animals are quite efficient. We humans have lost this capacity, but researchers are working incessantly to control cell reprogramming and make regenerative medicine possible and close at hand. It is probable that the ancient Greeks knew about the regenerative properties of the liver. Suffice it to recall the story of Prometheus. Different organs are considered: brain, heart, lung, kidney, adrenal glands, liver, pancreas, gut. Last but not least, we consider the stem cells of mother’s milk which, from the neonatal intestinal lumen, are transported to the several organs, among which the brain, in which they become neurons, oligodendrocytes and astrocytes. This is a discovery that changes many things with respect to our knowledge today. Many actors are present on the stage in the archipelago of complexity and the uninterrupted string of perinatal programming which, from fetus to adult, orients and governs our health, for better or for worse. Proceedings of the 2nd International Course on Perinatal Pathology (part of the 11th International Workshop on Neonatology · October 26th-31st, 2015) · Cagliari (Italy) · October 31st, 2015 · Stem cells: present and future Guest Editors: Gavino Faa, Vassilios Fanos, Antonio Giordano